Sul riciclo dei porcellini: il problema del consumo di carne contaminata - Bednarek, Bartlomiej (O T I V M, 2017)
The paper discusses the status of piglets used at some point of initiation in Eleusinian Mysteries. According to scholarly tradition two scenarios are possible: the piglets were either used as katharmata and subsequently discarded as contaminated or they were sacrificed to some deities and at least partially eaten by human participants in the ritual. The passage from Aristophanes’ Frogs discussed in the paper is usually taken as a strong evidence in favour of that latter interpretation. This reading, as I argue, does not give justice to its function within Aristophanic comedy.